A Smart Drug Delivery System Based on Biodegradable Chitosan/Poly(allylamine hydrochloride) Blend Films - Muhammad Sohail Sarwar; Qingrong Huang; Abdul Ghaffar; Muhmmad Amin Abid; Muhammad Sohail Zafar; Zohaib Khurshid; Muhammad Latif (MDPI AG, 2020)
The amalgamation of natural polysaccharides with synthetic polymers often produces fruitful results in the area of drug delivery due to their biodegradable and biocompatible nature. In this study, a series of blend films composed of chitosan (CS)/poly(allylamine hydrochloride) (PAH) in different compositions were prepared as smart drug delivery matrices. The properties of these polymeric films were then explored. Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) analysis confirmed an intermolecular hydrogen bonding between CS and PAH. Atomic force microscopy (AFM) revealed improvements in surface morphology as the percentage of PAH in the blend films increased up to 60% (w/w). Water contact angle (WCA) ranged between 97° to 115°, exhibiting the hydrophobic nature of the films. Two films were selected, CTH-1 (90% CS and 10% PAH) and CTH-2 (80% CS and 20% PAH), to test for in vitro cumulative drug release (%) at 37 ± 0.5 °C as a function of time. It was revealed that for simulated gastric fluid (SGF) with pH 1.2, the cumulative drug release (CDR) for CTH-1 and CTH-2 was around 88% and 85% in 50 min, respectively. Both films converted into gel-like material after 30 min. On the other hand, in pH 7.4 phosphate buffer saline (PBS) solution, the maximum CDR for CTH-1 and CTH-2 was 93% in 90 min and 98% in 120 min, respectively. After 120 min, these films became fragments. Sustained drug release was observed in PBS, as compared to SGF, because of the poor stability of the films in the latter. These results demonstrate the excellent potential of blend films in sustained-release drug delivery systems for hydrophilic or unstable drugs.